Variability in L2 Vowel Production: Different Elicitation Methods Affect Individual Speakers Differently - Munro, Murray J. (Frontiers in Psychology, 2022)
Elicitation methods are known to influence second language speech production. For teachers and language assessors, awareness of such effects is essential to accurate interpretations of testing outcomes. For speech researchers, understanding why one method gives better performance than another may yield insights into how second-language phonological knowledge is acquired, stored and retrieved. Given these concerns, this investigation compared L2 vowel intelligibility on two elicitation tasks, and the degree to which differences generalized across vowels, vowels in context, lexical items and individual speakers. The dependent variable was the intelligibility of Cantonese speakers’ productions of English /i ɪ u ʊ/ in varying phonetic environments. In a picture naming task, the speakers produced responses without an auditory prompt. In a second task – interrupted repetition – they heard exemplars of the same targets without pictures, and repeated each one after counting aloud to 10, a step intended to disrupt their short-term auditory store and therefore prevent simple mimicry. For target words with scores below 80% on picture naming, mean intelligibility was more than 10 points higher on interrupted repetition. However, that difference did not generalize across conditions or across speakers. Thus, although it is technically accurate to say that, on average, interrupted repetition yielded better vowel intelligibility than did picture naming, that observation requires a great deal of qualification, particularly because of individual speaker differences. The outcomes are interpreted in terms of their relevance to language assessment and to phonetic learning.